Effect of temperature induced bond degradation on fire response of reinforced concrete beams. (1st July 2017) - Kodur, V.K.R.; Agrawal, Ankit
Highlights: Effect of bond degradation on fire resistance of concrete beams is studied. Effect of major factors influencing high temperature bond degradation is quantified. Phenomena that lead to bond-slip at high temperature are explained. Abstract: The influence of temperature induced bond degradation on response of reinforced concrete (RC) beams exposed to fire is presented. A finite element based numerical model is developed in ABAQUS for tracing the response of reinforced concrete beams exposed to fire. Temperature induced interfacial bond degradation between concrete and reinforcing steel is specifically taken into account using bond-link element approach. The effect of temperature dependent local bond stress-slip relations on fire resistance of both normal strength and high strength reinforced concrete beams is investigated. A comparison of numerical model predictions with response parameters measured in fire tests clearly indicate that interfacial bond between reinforcing steel and concrete can influence extent of strength degradation and deflections in RC beams exposed to fire leading to relatively lower fire resistance in the beams. Hence, the current approach of assuming a perfect bond between rebar and concrete in fire resistance analysis of reinforced concrete structures may be un-conservative in certain scenarios, especially for RC beams reinforced with smooth rebars and when rebar temperature exceeds 400 °C.